Management of Pakshaghat (Stroke) Using Panchakarma Therapies: A Case Report & Review - Anil Soni; Avvinish Narine; Gopesh Mangal (RGUHS Journal of AYUSH Sciences)
Stroke remains a major cause of mortality and morbidity in India with limited rehabilitation strategies available. This case report examines the efficacy of Panchakarma therapies in stroke Pakshaghat management offering a holistic approach to enhanced functional recovery. A 41-year-old male patient with Pakshaghat underwent six months of integrated Panchakarma treatment including Rasa Aushadhi Shashtika Shali Pinda Swedana Mushtadi Yapana Basti Shirodhara Dashmoola Siddha Ksheera and Nasya Ksheerbaladi Taila. Notable improvements were observed particularly in muscle strength and independent mobility. These outcomes suggest Panchakarmarsquos therapeutic potential in enhancing stroke recovery. The report emphasizes the need for further scientific evaluation of Ayurveda-based rehabilitation and proposes the integration of Panchakarma with conventional medicine as a promising adjunctive strategy.nbsp